COVID-19 vaccination coverage among travellers at Lomé international airport (Togo), in 2022 - Atèhèzi Adom; Kossivi Agbélénko Afanvi; Arnold Junior Sadio; Latame Komla ADOLI; Roméo Medessè Togan; Martin Kouame Tchankoni; Yao Rodion Konu; Fifonsi Adjidossi Gbeasor-Komlanvi; Takpaya Gnaro; Panaveyi Malou Adom; Didier Koumavi Ekouevi (AOSIS, 2024)
Introduction: COVID-19 pandemic management leads to new health policies including the requirement of a vaccination pass or a negative Polymerase Chain Reaction (PCR) test for cross-border flights. The objective of this study was to estimate COVID-19 vaccination coverage among travellers, as well as factors associated with a full vaccination. Materials and Methods: A cross sectional study was conducted in July 2022 at the Gnassingbé Eyadema International Airport (LFW) in Lomé. Travellers met at LFW, aged 12 years or above, and who agreed to participate in the study have been submitted a questionnaire. Logistic regression analysis was performed to identify factors associated with full vaccination defined as having received at least two doses of COVID-19 vaccine according to a validated vaccine schedule. Results: A total of 847 travellers were included. 67% were men The median age was 40 years, Interquartile Range [31-48]. The main health document presented by travellers was the vaccination pass (69.1%). The majority (84.4%) of travellers had received at least one dose of COVID-19 vaccine and 63.9% had received at least two doses. Being 40 years of age or above (aOR=1.42; p=0.046), and travelling from a country outside Africa (aOR=2.18, p=0.003), were positively associated with full vaccination. Conclusion: Vaccination coverage among travellers at the LFW was relatively high. Travellers from a region outside Africa and aged 40 years or above were more likely to be full vaccinated. Better communication and strengthening of the vaccination strategies in Africa could help reduce these gaps.